2003
DOI: 10.1186/1475-925x-2-9
|View full text |Cite
|
Sign up to set email alerts
|

Feature extraction for the analysis of colon status from the endoscopic images

Abstract: BackgroundExtracting features from the colonoscopic images is essential for getting the features, which characterizes the properties of the colon. The features are employed in the computer-assisted diagnosis of colonoscopic images to assist the physician in detecting the colon status.MethodsEndoscopic images contain rich texture and color information. Novel schemes are developed to extract new texture features from the texture spectra in the chromatic and achromatic domains, and color features for a selected r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 15 publications
0
28
0
2
Order By: Relevance
“…Studies of BPNN suggest that increasing the number of hidden neurons improves classification accuracy[23, 24] and a large decay rate results in non-convergence[22]. Thus, the value of decay and the number of hidden units of the hidden layer were tuned when running a backward propagation neural network with sigmoid activation functions in the hidden and output layers.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of BPNN suggest that increasing the number of hidden neurons improves classification accuracy[23, 24] and a large decay rate results in non-convergence[22]. Thus, the value of decay and the number of hidden units of the hidden layer were tuned when running a backward propagation neural network with sigmoid activation functions in the hidden and output layers.…”
Section: Methodsmentioning
confidence: 99%
“…The group of Krishnan et al as well as Tjoa et al have suggested several image processing approaches for the automated detection of polyps and other lesions in colonoscopic images, including the description of the lumen area and its boundary by statistical features and form factors [7], edge-based features [8], local binary patterns (LBPs) [9], homogeneity histograms [10], as well as texture spectrum [11]. While the contour of the colonlumen is calculated solely in the intensity domain, local statistical features, LBPs and texture spectrum are calculated on different color planes, including saturation, hue and intensity, and the planes from the RGB color space.…”
Section: Overviewmentioning
confidence: 99%
“…Redness may specify bleeding and black may be treated as deposits due to laxatives. Green may be the presence of faecal materials, which are not clear during the preoperative preparation, and yellow relates to pus formation (Tjoa and Krishnan, 2003).…”
Section: Colon Cancer: Clinical Characterizationmentioning
confidence: 99%